DOP33 Role of adherent and invasive E. coli in Crohn's Disease: Lessons from the postoperative recurrence model. (21st January 2022) - Buisson, A; Sokol, H; Hammoudi, N; Nancey, S; Treton, X; Nachury, M; Fumery, M; Hébuterne, X; Rodrigues, M; Hugot, J P; Boschetti, G; Stefanescu, C; et al.
Abstract: Background: We used the postoperative recurrence model to better understand the role of AIEC bacteria in Crohn's disease (CD), taking advantage of a well-characterized postoperative cohort. Methods: From the REMIND prospective, multicenter cohort of operated CD patients (ileocolonic resection), AIEC identification was performed within the surgical specimen (M0) (N=181 patients) and the neo-terminal ileum (n=119 patients/181) during colonoscopy performed 6 months after surgery (M6). Endoscopic postoperative recurrence was graded using Rutgeerts' index, which was interpreted, either from a clinical point of view (postoperative endoscopic recurrence ≥ i2b or severe ≥ i3), or from a pathophysiological point of view (reappearance of the first ileal lesions = i1 and more advanced postoperative ileal recurrence = i2b + i3). The mucosa-associated microbiota was analyzed by 16S sequencing at M0 and M6. Relative risks (RR) or odds ratios (OR) were adjusted on potential confounders ((gender, smoking, CD duration, CD phenotype, prior bowel resection, indication for surgery, granuloma, preventive treatment, antibiotics). Results: Among the 228 patients included at the time of the analyzes, the search for AIEC was carried out in 181 patients at M0, and 119 patients at M6. Among these 181 patients included in our study, 46.3% did not receive any preventive treatment for endoscopic postoperative endoscopic recurrence while 24.3% have been treated with anti-TNF to prevent postoperative recurrence. AIEC prevalence was two-fold higher within the neo-terminal ileum at M6 (30.3%) than within the surgical specimen (14.9%) (p<0.001). AIEC within the neo-terminal ileum at M6 was associated with higher rate of early ileal lesions (i1) (41.6% vs 17.1%; aRR=3.49[1.01–12.04], p=0.048) or ileal lesions (i2b + i3) (38.2% vs 17.1%; aRR=3.45[1.06–11.30], p=0.040) compared to no lesion (i0). AIEC within the surgical specimen was predictive of higher risk of i2b-endoscopic POR (aOR=2.54[1.01–6.44], p=0.049) and severe endoscopic POR (aOR=3.36 [1.25–9.06], p=0.017). While only 5.0% (6/119) of the patients were AIEC-positive at both M0 and M6, 43.7% (52/119), patients with history of AIEC infection (M0 or M6) had higher risk of ileal endoscopic POR (aOR=2.32 [1.01–5.39], p=0.048]), i2b-endoscopic postoperative recurrence (aOR = 2.41[1.01–5.74]; p=0.048) and severe endoscopic postoperative (aOR = 3.84[1.32–11.18], p=0.013). AIEC colonization was associated with a specific microbiota signature including increased abundance of Ruminococcus gnavus . Conclusion: Based on the postoperative recurrence model, our data support the role of AIEC in the early steps of ileal CD.